The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
https://uqam-bib.on.worldcat.org/oclc/953804743
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Dictionnaire des cultures gays et lesbiennes - Eribon, Didier; Haboury, Frédéric; Lerch, Arnaud (Larousse, 2003)
Dictionnaire illustré et international consacré aux cultures gays et lesbiennes contemporaines (depuis la fin du XIXe siècle). Plus de 570 articles(2 millions de signes en tout), dont 50 dossiers thématiques, qui couvrent tous les aspects du sujet : - références culturelles et artistiques communes (d'Absolutely Fabulous à Virginia Woolf, de Pedro Almodóvar à Andy Warhol.), - associations (Act Up.), - théoriciens (Michel Foucault.), - événements (Lesbian and Gay Pride.), - mours et modes de vie (sida, sexualités.), - aspects légaux (couple, adoption.), - gay and lesbian studies (histoire, sociologie, queer theory.), etc.
Section: 548 pages : illustrations (certaines en couleur), photogr. (certaines en couleur) ; 27 cm
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; histoire et politique; militance; outils; ouvrages de références; premier cycle; périodes historiques; queer; sexualité; soc2014; thématiques; études gaies et lesbiennes